Hemodialysis Catheters: Update on Types, Outcomes, Designs and Complications - El Khudari, Husameddin; Ozen, Merve; Kowalczyk, Bridget; Bassuner, Juri; Almehmi, Ammar (Seminars in Interventional Radiology, 2022)
Hemodialysis catheters (HDCs) are an essential part of kidney replacement therapy. While these catheters are considered only the bridge to long-term vascular access such as arteriovenous fistulas and grafts, they are associated with significant morbidity and mortality and subsequent increased health care expenditures. However, despite these risks, a large proportion of end stage kidney disease population initiates dialysis using these catheters. The pathogenicity of HDCs stems from its invasive nature to the venous vasculature tree resulting in both mechanical and infectious complications. Therefore, the wide use these catheters in dialysis population and the associated complications necessitated continuous innovations in the catheter material, design, and placement techniques. This review provides an update on the catheter types, catheter tip designs, and the new technologies and innovations aimed to improve the catheter functionality and mitigate its related complications.
Keywords: hemodialysis; dialysis catheter; end-stage renal disease; catheter-related bloodstream infection; fibrin sheath